Answer:
y = 8x - 2
Step-by-step explanation:
slope intercept form is y = mx + b
m = slope
b = yintercept
Answer:
3 7/12 kg
He doesn't have enough plant to feed strawberry 2 more times and tomato 1 more time
Step-by-step explanation:
On sunday , sheldon bought 4 1/2 kg of plant food. He uses 1 2/3 kg on his strawberry plants and used 1/4 kg for his tomato plants. b. Sheldon wants to feed his strawberry plants 2 more times and his tomato plants one more time. He will use the same amounts of plant food as before. How much plant food will be need? Does he have enough left to do so.
Total plant bought = 4 1/2 kg
Strawberry = 1 2/3 kg
Tomato = 1/4 kg
Strawberry + tomato
= 1 2/3 + 1/4
= 5/3 + 1/4
= 20+3/12
= 23/12 kg
Total remaining after Sunday
= Total - used
= 4 1/2 - 23/12
= 9/2 - 23/12
= 54-23/12
= 31/12
= 2 7/12 kg
Sheldon wants to feed his strawberry plants 2 more times and his tomato plants one more time.
Strawberry = 2 × 1 2/3
= 2 × 5/3
= 10/3 kg
Tomato = 1 × 1/4
= 1/4 kg
Total plant needed to feed strawberry two more times and tomato 1 more time
= 10/3 kg + 1/4 kg
= 40+3/12
= 43/12 kg
= 3 7/12 kg
He will need 3 7/12 kg of plant
He doesn't have enough plant to feed strawberry 2 more times and tomato 1 more time
Answer:
369
Step-by-step explanation:
g(f(x)) simply means to put the whole expression of function f(x) into the place of "x" in g(x).
and to find the functional value for a specific x we just need to calculate functional value for f(x) and use that result as input for g(x).
f(6) = 8×6 + 5 = 48 + 5 = 53
and now
g(53) = 7×53 - 2 = 371 - 2 = 369
to check we do the general functional substitution :
g(f(x)) = 7×(8x+5) - 2 = 56x + 35 - 2 = 56x + 33
g(f(6)) = 56×6 + 33 = 336 + 33 = 369
correct
The absolute value of x is simply x and followed by the expression.
X + 1 + x + 1 <_ 2
2x + 2 <_ 2
2x <_ 0
X <_ 0
Basically all values that follow this inequality will most likely hold true.
For instance. -1.
-1 + 1 = 0
Absolute value of -2 = 2.
2 is equal to 2. This expression holds true.
Answer:
Solution: (-4, 2), x= -4 and y =2
Step-by-step explanation:
-8x - y = 30
-2y = x
Substitute for x
-8*(-2y) - y = 30
16y - y = 30
15y = 30
y = 30/15 = 2
Then x = -2y = -2*(2) = -4
Solution: (-4, 2), x= -4 and y =2